Coordination between water source partitioning and isohydric-anisohydric behavior shapes contrasting water use strategies of Tamarix chinensis and Ulmus pumila in saline-alkaline soils - Wang, Ting; Dong, Chenguang; Wan, Hui; Zou, Rongsong; Ren, Ranran; Yu, Shouchao; Xie, Xian (Frontiers in Plant Science, 2025)
Plant water-use strategies are key functional traits for survival in water-limited ecosystems. Understanding how water uptake coordinates with physiological characteristics in coastal saline-alkaline environments is crucial for explaining drought adaptation. However, the specific responses of these strategies to water stress in such ecosystems remain unclear. In this study, we used hydrogen and oxygen stable isotope (δ2H and δ18O) combined with a MixSIAR model to quantify seasonal variations in water uptake patterns of Tamarix chinensis and Ulmus pumila in the Yellow River Delta, China. Concurrently, we measured key physiological parameters, predawn and midday leaf water potential (Ψpd, Ψmd) and stomatal conductance (gs), to assess their iso-/anisohydric behavior. Redundancy analysis (RDA) was further used to explore the coordination between water uptake patterns and iso-/anisohydric strategies. T. chinensis exhibited a plastic water uptake strategy, adjusting water sources with seasonal aridity, and showed anisohydric behavior characterized by larger ΔΨ and weak gs sensitivity. In contrast, U. pumila maintained a conservative strategy, relying mainly on middle (33%) and deep soil water (31%) throughout the season and displayed isohydric behavior by tightly regulating gs under declining Ψmd. The distinct water uptake patterns of both species were tightly coordinated with their respective iso-/anisohydric behaviors and associated physiological traits. Anisohydric plasticity in T. chinensis provides greater adaptability to variable precipitation, whereas the conservative isohydric strategy of U. pumila may reduce drought resilience. These insights can guide species selection and management to improve drought tolerance in saline-alkaline coastal plantations.